CATION MIXING IN NATURAL MGAL2O4 SPINEL: A HIGH-TEMPERATURE 27AL NMR STUDY - Maekawa H.; Kato S.; Kawamura K.; Yokokawa T. (My University, 1997)
The positional disorder of Mg2+ and Al3+ cations between the tetrahedral and octahedral sites in natural MgAl2O4 spinel has been investigated by 27Al MAS NMR at room temperature and in-situ high-temperature 27Al NMR spectroscopy up to 1600 °C. The inversion parameter describing the disorder, x, where x stands for the positional disorder between Mg and Al cations in Mg1–xAlx(MgxAl2–x)O4, increased with temperature. Below 1100 °C the inversion parameter, x, can be determined from MAS NMR measurements of quenched samples at room temperature. Above 1100 °C, x was estimated from the peak position in the high-temperature 27Al NMR spectra up to 1600 °C. The observed dependence of x with temperature was fitted using the model of O’Neill and Navrotsky (1983). The coefficients of the model obtained are α = 35 ±5 kJ and β = –32 ±5 kJ, which are approximately equal in magnitude and opposite in sign. The x values observed in the present investigation are in agreement with the model. However the introduction of an additional entropy term, ΔSD, improved the fitting. ΔSD reduces the entropy of disorder relative to a random mixing model. This would reflect either a nonconfigurational entropy contribution or short-range Mg-Al order because of local charge balance. On the other hand, above 1400 °C a narrow peak appeared at about 60 ppm. This peak became narrower with increasing temperature up to 1600 °C. This behavior might suggest that a rapid exchange process among the fourfold-coordinated Al sites occurs in this temperature range.